Treating problem solving deficits in traumatic brain injury - Kelkar, Amit S. (East Carolina University, 2014)
Cognitive deficits following TBI are multidimensional. Current treatment programs approach problem solving training in a top-down approach with problem solving skill perceived independent of attentional control and working memory. Also, these treatment programs lack sufficient evidence-based data to support maintenance and generalization. The current study takes a bottom-up approach where set-shifting (attention), updating (working memory) and inhibition were targeted in an individual setting to improve problem solving skills for individuals with TBI. Three participants with a history of moderate-severe TBI participated in the multiple-probe ABA design study. The multiple probe design included baseline, treatment and generalization probes administered through the course of the study. UPSA Letter- Number sequencing and Digit Span subtests of WMS-III and Color-word interference and Trail Making subtests of D-KEFSwere administered to obtain pre-treatment measures on problem solving skills, working memory, inhibition and attention respectively. Twenty treatment sessions of 1-hour duration were conducted across five weeks to improve working memory, attention and inhibition skills using paper-pencil and computer training tasks. Post-treatment probes were obtained 1-month after treatment to assess maintenance of learned skills. Results indicate large treatment effects for all participants with significant improvement in pre-post treatment measures of problem solving, memory, attention and inhibition skills. Treatment probe scores for problem solving skills were higher than baseline mean and trend for all participants. These positive trends provide preliminary data to support bottom-up approach. Targeting working memory, attentional and inhibition skills shows concurrent improvement in problem solving skills in individuals with TBI. Positive maintenance data and generalization results further strengthen this novel approach and paradigm shift in treating problem solving deficits.
Keywords: Speech Therapy; Cognitive psychology; Cognitive rehabilitation; Executive functions; Single subject design; Traumatic brain injuries; Neuropsychological Tests; Brain Injuries--psychology; Brain Injuries--rehabilitation; Cognitive Therapy--methods; Problem Solving